The evolution of creative industries - Skavronska, Iryna (Skhid, 2016)
The article is devoted to the problem of outlining the evolution of creative industries. The meaning of notions "creativity" and "creative industry" is highlighted. Major stages of the origin and development of creative industries, which are pre-industrial age, industrial age and post-industrial age, are identified. The comparative analysis of the evolution of creative industries throughout the centuries is carried out.